LITERACY FOR SOCIAL JUSTICE - Michelle McAnuff-Gumbs (Celt: A Journal of Culture, English Language Teaching & Literature, 2004)
Literacy has become a sitefor playing out the unjust social arrangements of hierarchy and inequity in our educational institutions, where minorities and marginalized 'others' predictably fail (Gilmore, 2003: 10). It isfor this reason that this paper examines teacher attitudes to obstacles to the establishment of literacy partnerships with parents of children of poverty. The intersection of such altitude with issues of equity of access to and participation in educational service has become the main focus. Teacher altitude is explored along eight dimensions grounded in the psychological literature. In terms of research, this paper discusses also the forces that contribute to failed or failing partnership efforts.